Validation of Herek’s attitudes toward lesbian women and gay men scale among undergraduates in mainland China - Wang, Junfang; Liu, Yusi; Fu, Guochen; Chen, Yifan; Wu, Lei; Pan, Mingliang; Yang, Yuli; Chen, Zhuo; Cao, Yu; Li, Yong; Wang, Hao; Wang, Bixiang; et al. (Frontiers in Psychology, 2022)
This study aims to validate Herek's attitudes toward lesbians and gay men (ATLG) scale among undergraduates in mainland China and determine the factors associated with ATLG. A total of 6,036 eligible undergraduates drawn from 30 provinces across China completed the self- designed online questionnaire. A confirmatory factor analyse was first performed to test the two- factor structure (ATL and ATG) of Herek's ATLG scale, Cronbach's alpha was then used to assess the internal consistency, Logistic regression analyses were finally carried out to identify their respective determinants. The findings indicated that the two-factor model fitted the data reasonably well and two subscales also had good internal reliability. Gender, major, causal attribution, adherence to traditional gender norms and exposure to homosexual content were significantly associated with both ATL and ATG, while sexual orientation and direct contact with homosexuals were significantly associated with ATG but not with ATL. Therefore, Herek's ATLG scale has been proven to be a reliable and valid tool that can be used to identify undergraduates with negative attitudes toward lesbians and gay men. Its two distinct constructs were determined by different factors and thus would be treated separately.